2022
DOI: 10.1093/ehjci/jeab290
|View full text |Cite
|
Sign up to set email alerts
|

Wall shear stress angle is associated with aortic growth in bicuspid aortic valve patients

Abstract: Aims Aortic wall shear stress (WSS) distributions in bicuspid aortic valve (BAV) patients have been associated with aortic dilatation, but prospective, longitudinal data are missing. This study assessed differences in aortic WSS distributions between BAV patients and healthy controls and determined the association of WSS with aortic growth in patients. Methods and results Sixty subjects underwent four-dimensional (4D) flow ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 24 publications
2
11
0
Order By: Relevance
“…Another inflammatory mediator, TLR9, was only significantly correlated in the subset of patients with BAV, which suggests there may be a relationship between TLR9 and BAV with vascular aging. BAV increases aortic wall stress, 48 which over time could lead to activation of TLR9, an area that will future investigation for verification. With increased mitochondrial dysfunction, mitochondrial DNA may be released and subsequently activate innate immune pathways including the TLR9, inflammasome, and STING pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Another inflammatory mediator, TLR9, was only significantly correlated in the subset of patients with BAV, which suggests there may be a relationship between TLR9 and BAV with vascular aging. BAV increases aortic wall stress, 48 which over time could lead to activation of TLR9, an area that will future investigation for verification. With increased mitochondrial dysfunction, mitochondrial DNA may be released and subsequently activate innate immune pathways including the TLR9, inflammasome, and STING pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have shown, comparing BAV patients to subjects with normal, tricuspid valves (TAV), that WSS is clearly increased in patients with BAV compared to TAV ( 6 , 11 , 35 ). Especially circumferential WSS and progression of helicity seem to have an impact on aortic growth ( 36 , 37 ). Heterogeneous distribution of WSS leads to different affections of the vessel wall, including elastic fiber thinning ( 38 ) as well as intima-media thickening and plaque induction in initiation of atherosclerosis ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…4D flow MRI has contributed to our understanding of the association between BAV and ascending aortic aneurysms ( 54 - 57 ). Eccentric flow, which is an abnormal transvalvular flow caused by bicuspid valvular morphology, is thought to be an important contributor to the aortopathy in patients with BAV ( 58 , 59 ). Lorenz et al showed that, compared to the normal helical flow in the ascending aorta and arch observed in patients with tricuspid AV, patients with BAV had a significantly higher absolute peak helicity throughout the thoracic aorta ( 54 ).…”
Section: Clinical Application Of Blood Flow Assessment In Aortic Diseasementioning
confidence: 99%